2018
DOI: 10.1016/j.ultsonch.2018.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-assisted heterogeneous activation of persulfate by nano zero-valent iron (nZVI) for the propranolol degradation in water

Abstract: This study investigated the degradation of propranolol (PRO), a beta (β)-blockers, by nano zero-valent iron (nZVI) activated persulfate (PS) under ultrasonic irradiation. Effects of several critical factors were evaluated, inclusive of PS concentration, nZVI dosage, ultrasound power, initial pH, common anions, and chelating agent on PRO degradation kinetics. Higher PS concentration, nZVI dosage and ultrasound power as well as acidic pH favored the PRO degradation. Conversely, anions and chelating agent took on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(26 citation statements)
references
References 46 publications
0
26
0
Order By: Relevance
“…It is reported that two electron transmission pathways were proposed on passivated ZVI in the PS activation process: defect corrosion and semiconductor effect (Hou et al 2021). The corrosion products generated randomly on the surface of nZVI contained defects such as grain boundaries or pits (Gao et al 2018), then the electrons passed from ZVI to PS through these defects. In addition, most iron oxides and hydroxides are semiconductors (Hou et al 2021).…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that two electron transmission pathways were proposed on passivated ZVI in the PS activation process: defect corrosion and semiconductor effect (Hou et al 2021). The corrosion products generated randomly on the surface of nZVI contained defects such as grain boundaries or pits (Gao et al 2018), then the electrons passed from ZVI to PS through these defects. In addition, most iron oxides and hydroxides are semiconductors (Hou et al 2021).…”
Section: Resultsmentioning
confidence: 99%
“…•− is provided in Table 4, which also highlights their positive/negative behavior along with the target pollutant under study. Propranolol −ve [83] p-Nitrosodimethylaniline 12.4 +ve (10-100 mM) in alkaline media −ve in acidic media [99]…”
Section: Effect Of Inorganic Anions 321 Chloridementioning
confidence: 99%
“…It is very common to combine a metallic catalyst (either homogeneous or heterogeneous) with radiation, such as UV and US. Combination of nZVI and ultrasound improved the propranol and 4-Chlorophenol degradation by more than 20% because US increased the mass transfer rate and dispersed the aggregation of nZVI [111,116]. Three different activators (Fe 2+ /sodium citrate/UV) have been combined for PS activation for carbamazepine removal, reaching removal efficiencies 2.6 to 5 times higher than the activation with each one of them separately [113].…”
Section: Hybrid Activation Treatmentsmentioning
confidence: 99%